Effect of size and site preference of trivalent non-magnetic metal ions (Al3+, Ga3+, In3+) substituted for Fe3+ on the magnetostrictive properties of sintered CoFe2O4 - Anantharamaiah, P. N.; Joy, P. A. (Journal of Physics D-Applied Physics, 2017)
The influence of size and crystallographic site preference of three non-magnetic isovalent metal ions of larger (In3+), comparable (Ga3+) and smaller (Al3+) sizes, substituted for Fe3+ in the spinel lattice of CoFe2O4 on its magnetostrictive properties is compared. For the different compositions in CoFe2-xMxO4 (M = In3+, Ga3+, Al3+ and 0 <= x <= 0.3), significant changes in the structural and magnetic parameters are observed with the degree of substitution, due to the size and site preferences. Magnetic and Raman spectral studies revealed that Al3+ is substituted for Fe3+ at both octahedral and tetrahedral sites for all compositions, whereas In3+ and Ga3+ are substituted for Fe3+ at the tetrahedral site only for x <= 0.2 and partly at the octahedral site for x > 0.2. Regardless of the differences in the ionic size, site preference and the magnetic properties, compositions in all three series with x = 0.1 showed almost equal magnitude of maximum magnetostriction (lambda(max) = similar to 230 ppm), marginally higher than that of x = 0 (217 ppm). However, at higher substituted compositions, lambda(max) is decreased with x, but the decrease is much faster for the Al-substituted compositions. The maximum strain sensitivity, [d lambda/dH](max), is also found to be comparable for all three compositions. The comparable magnetostriction characteristics and high strain at low magnetic fields for different substituted compositions at low levels of substitution are attributed to the local structural distortions associated with the inhomogeneous distribution of the substituted ions in the spinel ferrite lattice. The studies suggest ways to optimise the magnetostriction properties of properly substituted sintered cobalt ferrite for applications in sensors and actuators.